Kualitas Fisik Daging Paha Ayam Broiler Yang Direndam Dalam Cairan Fermentasi Kubis (Brassica Oleracea Var.Capitata) Selama Penyimpanan Suhu Dingin (±5°C) - Afriani; Ariska, Cahyani Desi; Handoko, Heru (Jurnal Ilmu Peternakan Indonesia, 2025)
Broiler chicken meat is one of the most widely consumed sources of animal protein due to its affordable price, favorable taste, and high nutritional value. However, this type of meat is highly perishable because of microbial activity, which shortens its shelf life. To address this issue, simple preservation methods are required to extend storage while maintaining meat quality. One potential method is cold storage combined with natural preservatives, such as cabbage fermentation liquid, which contains antimicrobial compounds produced by lactic acid bacteria.This study aimed to evaluate the effect of cold storage duration (±5°C) on the physical quality of broiler chicken thigh meat soaked in cabbage fermentation liquid. A total of 10 broiler chickens were used, and the experiment employed a completely randomized design with four treatments and five replications. The parameters observed were pH value, water-holding capacity, and cooking loss. The results revealed that storage duration had a highly significant effect (P<0.01) on all parameters. The pH remained stable until day 4 but increased significantly on day 6. Water-holding capacity increased with longer storage, while cooking loss decreased. All values were still within the normal range. In conclusion, up to six days of cold storage with cabbage fermentation liquid is effective in extending shelf life while preserving the physical quality of broiler chicken meat.